Food systems transformation through school meals: 8 things - Hunter, Danny (2024)
Presented at the Southeast Asia School Meals Summit: Accelerating Collaboration and Commitments in Southeast Asian Countries to Advance Human Capital Development and Food Systems Transformation in Siem Reap, Cambodia, between 18-20 November 2024. This presentation explored the concept of food systems transformation through "planet-friendly school meals," emphasizing its potential to drive sustainable and climate-resilient agricultural development.